2010
DOI: 10.1111/j.1439-0272.2009.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of spermatogenic activity of processed Shilajit in oligospermia

Abstract: The safety and spermatogenic activity of processed Shilajit (PS) were evaluated in oligospermic patients. Initially, 60 infertile male patients were assessed and those having total sperm counts below 20 million ml(-1) semen were considered oligospermic and enrolled in the study (n = 35). PS capsule (100 mg) was administered twice daily after major meals for 90 days. Total semenogram and serum testosterone, luteinising hormone and follicle-stimulating hormone were estimated before and at the end of the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 13 publications
(11 reference statements)
3
25
0
4
Order By: Relevance
“…Placebo, composed with microcrystalline cellulose, lactose and magnesium stearate, has neither stimulation nor inhibiting role on testosterone secretion or synthesis. Processed Shilajit (PS) containing biologically active component di-benzo-alpha-pyrone (DBP) is earlier reported to increase the spermatogenic activity in selected patients of oligospermia (Biswas et al, 2009), and the current study demonstrates that purified Shilajit increases the total and free testosterone levels in healthy volunteers.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Placebo, composed with microcrystalline cellulose, lactose and magnesium stearate, has neither stimulation nor inhibiting role on testosterone secretion or synthesis. Processed Shilajit (PS) containing biologically active component di-benzo-alpha-pyrone (DBP) is earlier reported to increase the spermatogenic activity in selected patients of oligospermia (Biswas et al, 2009), and the current study demonstrates that purified Shilajit increases the total and free testosterone levels in healthy volunteers.…”
mentioning
confidence: 59%
“…Oral LD50 was found to be >2000 mg kg À1 (Acharya et al, 1988;Ghosal et al, 1989), and Shilajit was proved to be safe at doses of 0.2-1.0 g per kg body weight when used chronically (Kelginbaev et al, 1973;Anisimov & Shakirzyanova, 1982;Fortan & Acharya, 1984;Al-Hamaidi & Umar, 2003). Clinical evaluation of spermatogenic activity of processed shilajit in oligospermia (Biswas et al, 2009) revealed that there was no alteration on objective features related to any systemic toxicities such as serum urea, uric acid, serum bilirubin, total protein, serum globulin, SGPT, SGOT and alkaline phosphatase (Biswas et al, 2009). Besides, it was also observed that there was a significant (P < 0.001) improvement in spermia (+37.6%), total sperm count (+61.4%), motility (12.4-17.4% after different time intervals), normal sperm count (+18.9%) and total testosterone (+23.5%) with concomitant decrease in pus and epithelial cell count compared with baseline value in 28 patients of oligospermia after 90 days of treatment with PS at a dose of 100 mg twice daily.…”
Section: Introductionmentioning
confidence: 99%
“…PS, doğal habitatın kaya rizosferlerindeki mikrobiyal metabolitler ile bitki ve organik humuslu maddelerin kompleks bir karışımın-dan oluşmaktadır ve birçok ülkede binlerce yıl-dır geleneksel tıp sistemlerinin (Ayurveda) bir parçası olarak kullanılmaktadır (13). Modern tıpta PS ile ilgili yapılan bir çalışmada, PS'nin toplam sperm sayısını, sperm hareketini, serum testosteron, follikül stimülan hormon (FSH) ve spermatogenezin başlaması ve devamı için gerekli olan lüteinizan hormon (LH) seviyesini önemli derecede artırdığı gösterilmiştir (14). PS serbest radikal seviyesinin baskılanması üzeri-ne de önemli derecede katkı yapmaktadır.…”
Section: Introductionunclassified
“…PS serbest radikal seviyesinin baskılanması üzeri-ne de önemli derecede katkı yapmaktadır. Polimerizasyona neden olan hidroksil radikaline karşı, metil metakrilat korumasını sağladığı ve etkili bir biçimde nitrik oksit serbest radikallerinin etkisini azalttığı ifade edilmiştir (13)(14)(15)(16) germinal epitelde ve seminifer tübül bazal membranında düzensizlikler, interstisyel alanda ödem gözlendi (Resim 3, 4). MTX+PS grubunda, germinal epitelde düzensizlik ve lümenine germinal epitel hücrelerinin dökülmüş olduğu birkaç tübül dışında herhangi bir patolojiye rastlanmadı (Resim 5, 6).…”
Section: Introductionunclassified
See 1 more Smart Citation